Penderitaan yang tercermin dalam cerita pendek Le Vagabond karya Guy de Maupassant - Rachmah, Kartika Dwi; Dewi, Evi Rosyani (Franconesia, 2023)
The purpose of this study is to gain comprehension of suffering in the short stories Le Vagabond by Guy de Maupassant and its relation to French Language Education. Suffering in this study refers to Stettbacher's theory which states that suffering is based on four characteristics of suffering. The method used in this study is a descriptive qualitative method with a semiotic-structural approach. The results of this study indicate that there are citations in the short story of Le Vagabond that reflect the characteristics of suffering. The datas in this study are citations of words, phrases, sentences, with meanings and contexts, specifically found as many as citations containing the characteristics of la tristesse (sadness), the characteristics of la difficulté dans la vie (difficulty in life), the characteristics of l'anxiété (anxiety) and the characteristics of le désespoir (desperation).